Implikasi Keteladanan Menurut 1 Timotius 4:12 bagi Pelayan Khusus di Jemaat GMIM Koinonia Ranomea Wilayah Amurang III - Viti Feibe Malendes; Jeane M. Tulung; J.N Gara (Peneliti.net, 2022)
The purpose of this research is to describe how to be exemplary according to 1 Timothy 4:12. To analyze the example of special ministers in the congregation of the Evangelical Christian Church in Minahasa Koinonia Ranomea, Amurang III Region. To describe how efforts to develop and maintain exemplary special ministers in the Evangelical Christian Church congregation in Minahasa Koinonia Ranomea Amurang III Region. This research is a descriptive qualitative research with a historical-critical approach. Data collected through observation, interviews, documentation data. From the results of the research findings, there are indications that: (1) The special servant has not carried out his duties as the responsibillity of a special servant. Spesial ministers are still not an example for church members (2) Factors that influence the role model of special servants, namely internal factors and external factors (3) The efforts made by special ministers in developing and maintaining exemplary.